Dialoguing about American Religious Pluralism: An Egyptian Response - Elgendi, Yosra (Journal of ecumenical studies, 2018)
The article examines American religious pluralism and tradition of religious freedom. It reports how religion as a competitor to national ideologies, as patriotism assumes similar sacredness and establishes what is right and wrong (lawmaking) and establishes power hierarchies. It mention that First Amendment of the U.S. Bill of Rights ensures that the political realm would be separate from the religious realm.